Uslûb Dalâlî (Semantic Style) Qur'anic Verses and Their Absorption in Nature Sentence Patterns for Learning - Cahyo, Agus Tri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study aims to analyze Uslûb Dalâlî or semantic style in Qur'anic Verses and its absorption in sentences for learning. This research is qualitative with a library research approach. Research data is a corpus of verses of the Makiyyah Qur'an with semantic style values. The source of the data is the Qur'an. Data collection techniques are carried out with documentation. At the same time, data analysis uses content analysis. There were four discourses as a result of the study. First is the aspect of takrar (repetition). That repetition is contained in QS. Al-Baqarah: 4, QS. Ali Imran: 54, QS. An-Nur: 40, and QS. An-Nur 45. The absorption of sentence patterns is further projected for learning, like learning that continues to be repeated and all knowledge considered useful. Secondly, the Qasr (focusing) aspect appears in QS. Al-Baqarah: 5, QS. Al-Baqarah: 254, and QS. An-Nisa: 151. Absorbing sentence patterns reduces learners’ readiness for learning and consistent and honest practice. Third, the number of mu'taridah (discontinuous structures). Marked in QS. Al-Baqarah: 24; QS. Al-Baqarah 116; and QS. Al-Mumtahanah: 110. Absorption of sentence patterns is good learning that must end with evaluation/assessment truth, iltifat (pronoun distillation) contained in QS. Al-Baqarah: 128, QS. Al-Baqarah: 159, QS Ali-Imran: 11; QS. Ali-Imran: 81, and QS. Al-Maidah: 13. The pattern of sentence absorption reduces to the need, to be honest in the educational process and punishment for undisciplined students. Thus, the Qur'an is the greatest literary book with multi-meaning in each verse unit.